Kelayakan dan Strategi Pengembangan Usaha Silo jagung di Gapoktan Rido Manah Kecamatan Nagreg Kabupaten Bandung - Elvirysma T. Nainggolan; Musa Hubeis; Deddy Muchtadi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
Corn silo business of Rido Manah Farmer Groups is one of 56 units of corn silo that was developed by the Department of Agriculture. This research aimed to (1) identify and analyze the feasibility of business development in corn silo of Rido Manah Farmer Groups, (2) identify the internal and external factors affecting business development in the corn silo of Rido Manah Farmer Groups, (3) determining the appropriate strategy of business development of corn silo at farmer group.Data collection method used was the primary and secondary data were conducted through literature search, documents and reports of related institutions. Analysis reveals that of average farm productivity of farmers obtained from Farmers Group was slightly higher (4.59 tons/ha) compared to non-member farmers group (4.29 tons/ha). Size of farm management efficiency could be viewed by using the coefficient of revenue and expense ratio (R/C). R/C Farmer Groups (1.82) as well as non members (1.71) was greater than one, this indicated whether or not affiliated with Farmer Groups, Corn farming remain efficient and profitable, because the reward obtained was still higher than the costs. Corn silo business of Rido Manah farmer groups had been well implemented. BEP was 1.646,38 tons/year;B/C ratio was 1.07; PBP was 2,78 years; NPV with Discount Factors (DF) 14% was Rp. 127.019.755,6 and IRR was21%. Those values showed that the corn silo business managed by Rido Manah Farmer Group was feasible. Sensitivity analysis showed that investment in the business unit of corn silo was vulnerable to an increase and decrease in corn prices where the value of eligibility criteria was not feasible. The total value of internal strategic matrix3.013,meaning that the business unit of Corn silo Rido Manah Gapoktan had this high internal factors and external strategic matrix in total of 3.019 showed the response given by the corn silo business of Rido Manah farmer groups to the external environment was high. The best strategic alternative analysis obtained 6 most effective strategic business performed by silo corn which link by (1) establishing partnerships, (2) increasing the role of managers, (3) developing of process of corn products, (4) active collaborating, (5) increasing the capacity of equipment and machinary, and (6) increasing production and productivity of corn farmers.